2005
DOI: 10.1159/000085003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metal Clusters Isolated from Blood Are Lethal to Cancer Cells

Abstract: Unfolding and subsequent aggregation of proteins is a common phenomenon that is linked to many human disorders. Misfolded hemoglobin is generally manifested in various autoimmune, infectious and inherited diseases. We isolated micrometer and submicrometer particles, termed proteons, from human and animal blood. Proteons lack nucleic acids but contain two major polypeptide populations with homology to the hemoglobin α-chain. Proteons form by reversible seeded aggregation of proteins around proteon nucleating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…All these metals, including zinc were found in a few mg/L concentrations in human blood (DIONEX 2009). Zn, Fe, and Cu nanoparticles were found in human and animal blood (Samoylov et al 2005). In our experiments we found that copper nanoparticles stabilized olfactory responses, so that amplitude of the responses sustains for a long time (Viswaprakash et al 2009a).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…All these metals, including zinc were found in a few mg/L concentrations in human blood (DIONEX 2009). Zn, Fe, and Cu nanoparticles were found in human and animal blood (Samoylov et al 2005). In our experiments we found that copper nanoparticles stabilized olfactory responses, so that amplitude of the responses sustains for a long time (Viswaprakash et al 2009a).…”
Section: Discussionsupporting
confidence: 52%
“…Superatoms having special electronic structure possess unusual chemical, physical properties, and may have high stability against aggregation and oxidation. We found a large number of stable metal nanoparticles in human and animal blood (Samoylov et al 2005). It would be important to learn if they are physiologically significant.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1, A and B) share similarities with a group of intriguing particles described previously in the blood under various names, including "microzymas," "protits," "somatids," "cancer bacteria," "pleomorphic bacteria," and "filterable bodies," among other terms (83)(84)(85)(86). Vodyanoy and colleagues (87) have reported that metal nanoclusters may form structures referred to as "proteons" when they bind to denatured proteins in various body fluids, such as blood. Based on these and similar observations (8 -17), we believe that the putative microzymas, protits, somatids, and related entities may represent a combination of various particles that form spontaneously in the blood during incubation, which may include MVs, mineralo-organic NPs, proteons, and cellular remnants.…”
Section: Discussionmentioning
confidence: 66%
“…This incorporates a high-aperture, cardioid annular condenser (www.scitech.com.au) unique to this system and which makes possible visualization of objects below 90nm in diameter in real time, including cellular samples in an unfixed, living, active state (Samoylov, et al, 2005;Vainrub, et al 2006). Because PMNs were treated gently, avoiding perturbations of column separation and elution, it became possible to reliably study a PMN continuously for extended times without the onset of granular clumping, membrane blebbing and other signs of impending apoptosis (Lodish, 2005).…”
Section: Methods and Proceduresmentioning
confidence: 99%